Biology and therapeutic potential of mesenchymal stem cell‐derived exosomes - Xunian, Zhou; Kalluri, Raghu (Cancer science, 2020)
Mesenchymal stem cells (MSC) are multipotent stromal cells with the potential to differentiate into several cell types. MSC‐based therapy has emerged as a promising strategy for various diseases. Accumulating evidence suggests that the paracrine effects of MSC are partially exerted by the secretion of soluble factors, in particular exosomes. MSC‐derived exosomes are involved in intercellular communication through transfer of proteins, RNA, DNA and bioactive lipids, which might constitute a novel intercellular communication mode. This review illustrates the current knowledge on the composition and biological functions as well as the therapeutic potential of MSC‐derived exosomes in cancer, with a focus on clinical translation opportunities. The biology and therapeutic potential of mesenchymal stem cell‐derived exosomes.